Effect of the placement capacitor bank on electrical power quality in the ILST fan drive system - Hermawan, Asep Dadan; Negara, I Made Yulistya; Nandar, Cuk Supriadi Ali; Prastawa, Andhika; Aryono, Nur Aryanto; Damara, Dio Randa; Dianti, Dwie Vannia; Nugraha, Heri (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Power quality is a critical aspect of the effective and dependable operation of electrical systems. In today's technologically advanced world, where industries rely significantly on electricity, understanding and maintaining power quality is critical. National Research and Innovation Agency (BRIN) has an important laboratory for aerodynamic testing technology service activities in Indonesia. This facility contains a closed wind tunnel, a DC drive system, and a DC electric motor. This innovative fan drive system employs a parallel DC drive system, with the master and slave motors connected to a master DC drive system and a slave DC drive system, respectively. The usage of a new system results in poor electrical power quality, with a power factor value of less than 0.85, resulting in higher electricity costs and increased current, which has an impact on other equipment, such as a rise in temperature. To improve the quality of electrical power according to standard operating procedures and lower electricity bills, the current work evaluated the new system using field tests and literature studies on the impact of installing capacitor banks in parallel DC motor systems to boost the power factor value. This evaluation aims to improve the quality of the ILST parallel electric power system by including a capacitor bank in each motor.